An Empirical Study on the Effect of Social Media Marketing in Perspective of Digital Literacy Level on Healthy Eating Attitude of Obese Women - Ozsan, İsmail (International Journal of Innovative Research in Medical Science, 2023)
Objective: In this prospective cross-sectional study, it was aimed to evaluate effect of social media advertisement and digital literacy level on healthy eating attitude of obese women. Methods: A total of 387 women, 234 of whom were non-obese and 153 obese, residing in the central district of İzmir in 2022 were subjected to the study. A questionnaire including demographic information form, Digital Literacy Scale and Attitude Scale towards Healthy Eating was applied to the participants. Results: Age, economic status, chronic disease, malnutrition and family obesity history distributions were significantly different between obese and non-obese groups (p<0.05). Body Mass Index (BMI) and Malnutrition (MN) means were higher in non-obese group, and digital literacy, Information on Nutrition (IN), Emotion for Nutrition (EN), Positive Nutrition (PN) and Healthy Nutrition Behavior (HNB) total scores were higher in obese group. The digital literacy level difference was significant between patient groups (p<0.05). Digital literacy was positively correlated with IN (r=0.184; p<0.01), and negatively correlated with positive nutrition (r=-0.326; p<0.01) and malnutrition (r=-0.142; p<0.05) in non-obese group. Digital literacy was negatively correlated with malnutrition (r=-0.255; p<0.05) in obese group. Digital literacy level has significant and negative correlation with HNB (r=-0.121; p<0.05). Conclusion: The level of digital literacy significantly affects the level of health knowledge, positive nutrition and malnutrition in non-obese women. In obese women, the relationship between digital literacy and only malnutrition is statistically significant.